Penyuluhan Pembuatan Kerajinan Tangan (Gelang, Kalung, Gantungan Kunci, dan Cincin) Menggunakan Manik Pada Ibu-Ibu di Perumahan Tiban Mas Residence - Meldra, Delia Meldra; Yopy Mardiansyah (LPPM ITEBA, 2026)
This community service activity aimed to enhance the skills, creativity, and entrepreneurial potential of women through training and counseling on bead-based handicraft production, including bracelets, necklaces, keychains, and rings. The activity was conducted at Tiban Mas Residence using counseling, demonstration, and hands-on practice methods. The results showed an improvement in participants’ technical skills, increased product design variations, and growing interest in developing small-scale handicraft businesses. Additionally, the activity strengthened social interaction and collaboration among participants. Therefore, bead-based handicraft training can serve as a sustainable community empowerment model within the creative economy sector.